Gestión de residuos sólidos urbanos y su incidencia ambiental en los cantones Valencia, Mocache y Caluma. - Vera Santos, María Betshabé (2020)
In all the cities of Ecuador they face the problem of environmental contamination due to the generation of solid waste and its inadequate management. These residues constitute a problem for public health and are the main sources of infection for the proliferation of vectors and diseases. This project's main objective is to analyze the solid waste management of the cantons: Valencia, Mocache and Caluma. To obtain the data, records of the amount of waste produced daily, in the homes, in the study cantons were used. The waste management model was carried out in the STELLA program to estimate the environmental impact generated by garbage in the cantons, for this, two scenarios were modeled, one current and the other optimized. The Canton Valencia generated the highest amount of solid waste, with a total of 2,728.677 kg, the Canton Mocache generated the least amount of solid waste with a total of 1463.00 kg. Organic waste was the most representative in the three cantons, with 91.35%; 30.41%; 96.97%, for Caluma, Mocache and Valencia respectively. The per capita production of solid waste was: 0.5454 kg for the canton of Valencia; 5123 kg for the Mocache canton and 0.4780 kg for Valencia. The optimized model indicated that in 12 months a total of 12,557 tons of waste to be confined would be generated; meanwhile, in the current scenario, a confinement of 20,910 tons is estimated. Key words: Solid waste, Environmental Impacts, I Model of administration, Integral Administration.